Seesaw Effect: Preferensi Rasional dalam Fenomena Pergeseran Konsumen Pertamina ke Shell - Zulfa Meutia Putri; Afryan Fahri Mahendra; Nikmatul Rizki; Qonita Alysia Salma Diandra; Anjani Mahestika Nurani; Waskito Waskito (Prodi Sosiologi FISIP Universitas Teuku Umar, 2025)
The trust crisis surrounding Pertamina following the fuel adulteration scandal prompted a notable shift in consumer preferences and exposed a conceptual gap in understanding how rational action is formed under conditions of institutional delegitimization. Previous studies tend to treat Weberian rationalities as discrete categories, leaving unexplored how these forms interact during episodes of reputational crisis. Employing a qualitative phenomenological approach with 12 participants, this study draws on in-depth interviews, field observations, and thematic coding analysis to examine consumer transitions from Pertamina to Shell. The findings reveal that consumer actions do not manifest as four isolated types but rather as a continuum of interwoven rationalities instrumental, economic, value-oriented, and traditional shaped dynamically by crisis experiences, accessibility, and everyday consumption habitus. These insights extend Weber’s theory of social action by demonstrating that rationalities are not static attributes but situational and fluid across contexts of uncertainty. The study further introduces the Seesaw Effect as a conceptual contribution, explaining how the erosion of Pertamina’s reputation simultaneously elevates Shell’s legitimacy. Practically, the findings underscore that institutional reputation, service integrity, and transparency are central determinants in sustaining public trust within competitive fuel markets.